Evaluation of ghrelin and leptin levels in obese, lean and undernourished children - Miljković, Mirjana N; Šaranac, Ljiljana M; Bašić, Jelena; Ilić, Mirjana; Đinđić, Boris; Stojiljković, Marija G; Kocić, Gordana; Cvetanović, Goran Z; Dimitrijević, Nebojša (Vojnosanitetski pregled, 2017)
Background/Aim. Energy homeostasis is a balance between energy intake and energy expenditure. Leptin and ghrelin are two orexitropic hormones with opposite effect on energy homeostasis. We investigated fasting ghrelin and leptin serum levels in children with different nutritional conditions. Methods. In 30 obese children of both sexes, aged from 6 to 17.67 years (mean 13.04 ± 2.95 years), fasting ghrelin and leptin levels were determined in the serum, along with auxological assessment and pubertal staging. Obtained values were analyzed and compared with those of the same parameters in 33 lean and 25 undernourished (UN) children. Results. Mean ghrelin/body mass (BM) ratio was the lowest in obese children (21.75 ± 12.60 pg/mL/kg), which was significantly different in comparison with that in lean and UN subjects. Mean leptin/BM ratio of 0.62 ± 0.86 pg/mL/kg in obese children was significantly higher than that in lean and UN children (p < 0.01 and p < 0.001, respectively). Ghrelin and leptin levels showed different profiles in obese, lean and UN children. An inverse relationship was discovered among study groups in  ghrelin/leptin and leptin/ghrelin ratios. Conclusion. Obese children, compared to other children, have significantly higher values of leptin, and UN children have significantly higher values of ghrelin per kilogram of body mass. The results also illustrate the inverse ratio of ghrelin and leptin, which has been demonstrated as a clinically reliable marker of the status of obesity or undernutrition in children, with significant implications concerning rather large variations in the concentration of these hormones in relation not only to the body mass but also to the children’s age.
Keywords: nutritional status; child; leptin; ghrelin; obesity